Planar Light Extinction Measurement of Soot Volume Fraction in Laminar Counterflow Diffusion Flames - Zhou, Jiwei; Zhou, Mengxiang; Ma, Liuhao; Wang, Yu (Frontiers in Mechanical Engineering, 2021)
Cost-effective and straightforward light extinction method has been extensively used for measurement of soot volume fraction (SVF) in sooting flames. The traditional pointwise measurement with translation stage suffers from relatively time-consuming operation and low spatial resolution. In the current study, planar light extinction method is processed by utilizing a CMOS camera to image the combustion field of counterflow diffusion flame (CDF) backlit with the lamp. Collimated and diffuse optical layout were adopted to explore the feasibility. Investigations of beam-steering effects are presented and discussed through a combination of computational fluid dynamics (CFD) and ray tracing simulations. Measured SVF are compared to the well-validated laser-induced incandescence (LII) measurements. Current measurements show that the diffuse optical layout is feasible and robust to provide accurate and more efficient measurement of the SVF in CDF with superior spatial resolution (21.65 μm).